Analysis of the Effect of Drug Management on the Level of Drug Availability in Central Sulawesi Province - Asmanur Asri Rendelemba; Sudirman; Finta Amalinda (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
The availability of essential medicines is one of the main indicators of healthcare service quality in primary health centers (Puskesmas). Inadequate medicine availability can hinder medical services and reduce public trust in healthcare facilities. Problems related to medicine availability are generally influenced by various aspects of the drug management cycle, ranging from planning to reporting. This study aimed to analyze the effect of drug management on the level of medicine availability in primary health centers in Central Sulawesi Province and to identify the most dominant influencing variables.This study employed a quantitative approach with a cross-sectional design. The study population consisted of all 219 primary health centers in Central Sulawesi Province, with a sample of 142 health centers selected using proportional random sampling. Data were collected through structured questionnaires administered to pharmaceutical personnel. The independent variables included planning, procurement, receiving, storage, distribution, and recording and reporting, while the dependent variable was medicine availability. Data were analyzed using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis using multiple logistic regression at a significance level of 0.05.The bivariate analysis showed that all drug management variables were significantly associated with medicine availability (p < 0.05). Multivariate analysis revealed that planning (p = 0.006; Exp(B) = 1.366), procurement (p = 0.006; Exp(B) = 1.365), and distribution (p = 0.016; Exp(B) = 1.346) were significant predictors of medicine availability. The regression model demonstrated a Nagelkerke R Square value of 0.406, indicating that 40.6% of the variation in medicine availability could be explained by the variables included in the model.It can be concluded that strengthening data-based planning, improving procurement effectiveness, and ensuring timely and accurate distribution are key factors in enhancing medicine availability at primary health centers. Integrated logistics information systems and capacity building for pharmaceutical personnel are necessary to ensure sustainable medicine availability.